Assessment of effect of various concentration of ketamine-propofol (ketofol) on haemodynamic parameters and LMA insertion conditions - Jain, Sunita; Rathore, Raju Singh; Modiwala, Ashfaq (International Surgery Journal, 2018)
Background: The purpose of this study is to compare the effect of various concentration of ketamine-propofol (ketofol) on LMA insertion condition and hemodynamic parameters. Methods: Hundred patients of ASA I, II, aged between 18-65 years, were randomized in group A, B, C and D, each consist of 26, 25, 25, 24 patients respectively. They were premedicated with injection GPL, injection midazolam, injection fentanyl and induced with ketofol in 1:1, 1:2, 1:3 and 1:4 ratio in Group A, B, C, D respectively. 60 seconds after induction LMA insertion condition including mouth opening, swallowing, coughing, head and body movements, laryngospasm, ease of LMA insertion, apnea time, and time of LMA insertion were recorded. They were scored 1 to 3. Hemodynamic parameters- heart rate, noninvasive blood pressure and SPO2 were recorded before induction (T1), immediately following induction (T2), immediately after LMA insertion (T3), 5mins after LMA insertion (T4) and 10 mins after LMA insertion (T5). Results: Total 100 patients were included in this prospective randomized double-blind study between April 2017 to March 2018. Pulse rate at (T3) was significantly lower (P-0.06) in group C and D. Diastolic BP was found lower at (T2) time (P-0.04) in group C and D. Apnea time was longest in group A (P-0.002) LMA insertion time was minimum in group B (P-0.008). Conclusions: Addition of low dose of ketamine in propofol favour LMA insertion, due to opposite effect on muscle tone, better relaxation but heart rate, blood pressure remains stable with 1:1, 1:2 ratio of ketofol.